2002
DOI: 10.1080/00140130210158419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hot and cold temperature exposure on performance: a meta-analytic review

Abstract: A meta-analysis to mathematically summarize the effect of hot and cold temperature exposure on performance was completed. The results from 515 effect sizes calculated from 22 original studies suggest that hot and cold temperatures negatively impact performance on a wide range of cognitive-related tasks. More specifically, hot temperatures of 90 degrees F (32.22 degrees C) Web Bulb Globe Temperature Index or above and cold temperatures of 50 degrees F (10 degrees C) or less resulted in the greatest decrement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
266
2
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(291 citation statements)
references
References 40 publications
12
266
2
11
Order By: Relevance
“…The magnitude, structure, and coherence of these responses support the hypothesis that the underlying mechanism is a reduction in the productivity of human labor when workers are exposed to thermal stress. The ergonomics and physiology of thermal stress in humans is well studied (21)(22)(23)(24)(25)(26), but has been absent from previous integrated assessments of global climate change impacts (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…The magnitude, structure, and coherence of these responses support the hypothesis that the underlying mechanism is a reduction in the productivity of human labor when workers are exposed to thermal stress. The ergonomics and physiology of thermal stress in humans is well studied (21)(22)(23)(24)(25)(26), but has been absent from previous integrated assessments of global climate change impacts (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Research has shown that exposure to temperatures under 10°C for durations greater than 2 hours can have a significant negative impact on physical and cognitive performance, as well as general health and comfort [8]. As was observed, all expeditions took place in <10°C temperatures and tended to last for more than 3 hours without a break.…”
Section: Resultsmentioning
confidence: 92%
“…Cold working conditions have been associated with painful musculoskeletal disorders [4], loss of manual strength and dexterity [5], increased occurrence of slips, trips and falls [6] and a variety of cognitive impairments which increase the risk of an accident [7]. These cognitive impairments can include limited attention, curtailed memory and reasoning ability and impulsiveness; even at moderate levels of stress [8,9]. Moreover, risk of cold-related impairment also increases with duration and intensity of exposure, highlighting the hazard of performing critical tasks in consistently cold environments [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low temperature exposures lead to an increased metabolic rate (Selman et al, 2000), elevated reactive oxygen species (ROS) (Venditti et al, 2004) and OS-induced tissue damage (Topp et al, 2000). It is possible that cold-stimulated high metabolic rates can alter blood lipid profiles and accelerate the development and progression of OS-related occupational hazards such as reduced cognitive performance in terms of memory, vigilance and concentration (Pilcher et al, 2002;Palinkas, 2001). In an earlier study, we demonstrated the hypolipidemic effects of vitamin E supplements with age in rats (Asha Devi et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%